PENGARUH KEALITAS PELAYANAN DAN PELAKSANAAN PROMOSI TERHADAP KEPUASAN KONSUMEN JASA KAMAR PADA ALPHA HOTEL PEKANBARU - Hesti Agustin; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at Alpha Hotel Pekanbaru which is located at Jalan H. Imam Munandar No. 17 Pekanbaru. This study aims to determine the effect of Service Quality and Promotion Implementation on Room Service Consumer Satisfaction partially and simultaneously. This study uses a quantitative descriptive analysis method with the SPSS program. The population in this study were all visitors to Alpha Hotel Pekanbaru in 2020. The sample in this study was 100 respondents. Determination of the sample in this study using the Slovin formula, namely the Accidental Sampling technique.Data analysis used validity test, reliability test, classical assumption test, simple linear regression analysis, multiple linear regression analysis, determination analysis and significance test with t test (partial test) f test (simultaneous test). The results of this study indicate the results of the first t-test hypothesis, Service Quality has a significant effect on consumer satisfaction. Second, the implementation of the promotion has a significant effect on consumer satisfaction. The results of the f-test of Service Quality and Promotion Implementation simultaneously have a significant effect on Room Service Consumer Satisfaction at Alpha Hotel Pekanbaru.Keywords: Service Quality, Promotion Implementation, Consumer Satisfaction